Preparing for an Enterprising Future: A Multi-Case Study of the Role of Enterprise in New Zealand Schools - Nagel, Sabrina (Auckland University of Technology, 2023)
The integration of 'enterprise' or 'entrepreneurship' education into global education systems has gained significant popularity over the past decades. In the wake of the global pandemic, these educational concepts have been recognised as instrumental tools for driving economic recovery. However, despite their prominence, the precise distinctions between the two terms and the potential benefits they offer to the student body remain inadequately understood and underappreciated. To address this knowledge gap, this study adopted a critical realist ontology and a constructivist epistemology to investigate how enterprise is conceptualised and promoted in the context of a New Zealand school system. A multi-site case study was conducted, involving interviews with teachers and principals from four distinct schools. Additionally, a student focus group provided student insights. Complementing these primary data sources, document reviews were utilised to supplement the research findings. The adoption of a critical realist perspective offered a nuanced understanding of the complex interactions between various factors influencing enterprise education, while the constructivist epistemological stance facilitated an exploration of the cognitive processes and educational practices that shape students' entrepreneurial skills and mindset. By exploring the practical implementation and perceptions of enterprise education in New Zealand schools, this study is a contribution to the existing knowledge base. The findings are anticipated to benefit educational policymakers, school administrators, and curriculum developers by providing evidence-based recommendations for enhancing the effectiveness of enterprise education initiatives in the New Zealand context and beyond. Ultimately, this research represents an effort to advance the understanding of enterprise education's role in fostering economic resilience and innovation, empowering students to become dynamic contributors to their communities and economies.